Constructing kansei engineering methodology based on consumer experiences in children's luggage - Wang, Mingrun; Shaari, Nazlina; Perumal, Velu (PalArch Foundation, 2020)
Nowadays, there are many children’s luggage on sale in the Chinese market. However, the proportion of child renowning children’s luggage is still low. The lack of correct value determination of children’s luggage leads to consumers not having the desire to buy the luggage. Furthermore, understanding consumer experiences is the key to determine the value of children’s luggage. Previous researches did not analyse the consumer experiences of children’s luggage. The lack of understanding of the consumer experiences of children’s luggage leads to the value of the luggage cannot be correctly determined. These two problems have caused children’s luggage to lose their competitive advantages in the children’s consumer market. Therefore, this study targets to support the sales of children’s luggage and enhance the development of children’s luggage industry through using Kansei Engineering methodology. The findings found that the performance and appearance of children’s luggage were the two important components that parents will pay attention to when purchasing a luggage for their children. Children’s luggage with more convenience, comfortableness, safety, durability, pleasure and authority have a higher competitive advantage. Design elements of simple internal structure, convenient sliding moving mode, simple pull/push moving mode, smooth and hard shell, comfortable and soft shell, flexible and stable double row wheel, comfortable U-shaped telescopic handle, comfortable button opening mode, smooth or functional shape should be selected to design a high value children’s luggage. The findings will help designers to design a children’s luggage that provides more competitive advantages, thus promoting children's luggage sales and improving the children's luggage industry.